2015
DOI: 10.1007/jhep11(2015)064
|View full text |Cite
|
Sign up to set email alerts
|

Wilson loops and chiral correlators on squashed spheres

Abstract: Abstract:We study chiral deformations of N = 2 and N = 4 supersymmetric gauge theories obtained by turning on τ J tr Φ J interactions with Φ the N = 2 superfield. Using localization, we compute the deformed gauge theory partition function Z( τ |q) and the expectation value of circular Wilson loops W on a squashed four-sphere. In the case of the deformed N = 4 theory, exact formulas for Z and W are derived in terms of an underlying U(N ) interacting matrix model replacing the free Gaussian model describing the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
2
40
0
1
Order By: Relevance
“…The basic observation in understanding the duality at this level is the strong evidence that the chiral ring of the gauge theory retains the structure of integrals of motion, so chiral trace relations should emerge in a very natural way in this setup. This is clear in particular from the results of [30,31] for the SU (2) N = 2 theory with N f = 4 fundamentals hypermultiplets. As stated by AGT duality, this theory is related to a Liouville CFT on the 4-punctured sphere, with the instanton partition function being identified with the 4-point conformal block.…”
Section: Agt Interpretationmentioning
confidence: 92%
See 1 more Smart Citation
“…The basic observation in understanding the duality at this level is the strong evidence that the chiral ring of the gauge theory retains the structure of integrals of motion, so chiral trace relations should emerge in a very natural way in this setup. This is clear in particular from the results of [30,31] for the SU (2) N = 2 theory with N f = 4 fundamentals hypermultiplets. As stated by AGT duality, this theory is related to a Liouville CFT on the 4-punctured sphere, with the instanton partition function being identified with the 4-point conformal block.…”
Section: Agt Interpretationmentioning
confidence: 92%
“…2 The authors of [30,31] found a simple relation between the vacuum expectation values of chiral trace operators and the CFT correlation function with charge insertions: where V α are primary fields in this extended algebra with conformal dimension Δ α = α(Q − α). Guided by these results, in [25] we searched for similar relations in the SU (2) N = 2 * and pure gauge theories.…”
Section: Agt Interpretationmentioning
confidence: 99%
“…7 To be clear, this means the correction O(g 4 YM ) with respect to the tree level value. 8 See also [55] for a discussion in terms of Alday-Gaiotto-Tachikawa duality.…”
Section: Introductionmentioning
confidence: 99%
“…Let us find now a connected correlator between a WL in a symmetric representation and a chiral primary operator. This correlator can be written via matrix model integrals [5].…”
Section: Correlators Of a Symmetric Wilson Loop And Chiral Primary Opmentioning
confidence: 99%